Modeling water‐energy tradeoffs for cultivating algae for biofuels in a semi‐arid region with fresh and brackish water supplies. (12th September 2020) - Mayer, Alex; Tavakoli, Hossein; Fessel Doan, Ceily; Heidari, Azad; Handler, Robert
Abstract: We analyze water‐energy tradeoffs for hypothetical algae production for biofuel feedstock in the US‐Mexico middle Rio Grande watershed with a coupled water, salinity, and algae biomass balance model. Suitable areas for algae cultivation in the region are selected and associated with fresh or brackish groundwater sources. We examine the potential of using two algae species with markedly different energy content and tolerance to salinities. Location‐specific water quality and time‐varying climate variables were important when analyzing water‐energy tradeoffs for each species. In this regional study, water demand rates for the salinity‐tolerant species were similar to rates for conventional local crops, whereas the salinity‐sensitive species' values exceeded local demand rates. Optimizing the spatial selection of species resulted in water footprint reductions of as much as 18%. Water demand rates and footprints are highly sensitive to salinity and temperature tolerance and thus local variations in water quality and seasonal variations in climate. © 2020 Society of Chemical Industry and John Wiley & Sons, Ltd